2010
DOI: 10.1007/s11671-010-9780-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of Temperature in the Growth of Silver Nanoparticles Through a Synergetic Reduction Approach

Abstract: This study presents the role of reaction temperature in the formation and growth of silver nanoparticles through a synergetic reduction approach using two or three reducing agents simultaneously. By this approach, the shape-/size-controlled silver nanoparticles (plates and spheres) can be generated under mild conditions. It was found that the reaction temperature could play a key role in particle growth and shape/size control, especially for silver nanoplates. These nanoplates could exhibit an intensive surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
96
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(105 citation statements)
references
References 61 publications
8
96
1
Order By: Relevance
“…From this observation, the size of NSPs produced at 60°C was predicted smaller than the NSPs synthesized at 80°C. At low temperature, the formation and growth reaction was slower and in order to complete the reduction, it usually took longer reaction time (Jiang et al 2011). However, in this study, the reaction was immediately stopped once the dropping process of the precursor was complete.…”
Section: Results and Discussion Mechanism Prediction Of Nsps Formationmentioning
confidence: 82%
“…From this observation, the size of NSPs produced at 60°C was predicted smaller than the NSPs synthesized at 80°C. At low temperature, the formation and growth reaction was slower and in order to complete the reduction, it usually took longer reaction time (Jiang et al 2011). However, in this study, the reaction was immediately stopped once the dropping process of the precursor was complete.…”
Section: Results and Discussion Mechanism Prediction Of Nsps Formationmentioning
confidence: 82%
“…The silver molecules' aggregations are distributed among more numerous growth nuclei, resulting in a larger amount of nanoparticles with shorter average size. Other authors have reported the effects of growing metal nanoparticles at different temperatures (Jiang et al 2011), but besides this investigation, no work has yet been done in the effect of the initial heating rate. In a similar way, the different dimensions obtained for each species may be useful for the synthesis of certain desired ranges of size.…”
Section: Resultsmentioning
confidence: 91%
“…1, 2, 3, 4b). A variety of investigations on the synthesis of AgNPs have been done at fixed reaction temperatures, which have disclosed the importance of this parameter to characteristics such as the size and shape of the final product (Fayaz et al 2009;Jiang et al 2011). …”
Section: Resultsmentioning
confidence: 99%
“…In this reaction, citrate is used to convert Au (III) to Au (I), and create the NPs. By shifting some factors such as temperature, and the ratio of the administered compounds, it is possible to control both the size, and the distribution of the NPs 24, 25, 26…”
Section: Methodsmentioning
confidence: 99%